Toxicity of Thevetia peruviana (Pers) Schum. Extract to Adults of Callosobruchus maculatus F. (Coleoptera: Bruchidae) - Mollah, JU; Islam, W (Journal of Agriculture & Rural Development, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Leaf, stem and roots of Thevetia peruviana (Pers) Schum. were extracted in four organic solvents; petroleum spirit, ethyl acetate, acetone and methanol and tested against the adults of Callosobruchus maculatus F. All the tested extracts effectively produced mortality of C. maculatus and their toxicity was in order of solvents: petroleum spirit>ethyl acetate>acetone>methanol. Root extract was the most toxic to C. maculatus. Females were more tolerant than males. Key words: Extract, mortality, solvent, Thevetia peruviana, Callosobruchus maculatus. DOI = 10.3329/jard.v5i1.1466 J Agric Rural Dev 5(1&2), 105-109, June 2007